A Method for Determination of Ammonia in Air using Oxalic Acid-Impregnated Cellulose Filters and Fluorimetric Detection - Felix, Erika P.; Cardoso, Arnaldo Alves [UNESP] (Soc Brasileira Quimica, 2012)
A fluorimetric method was developed for the determination of ammonia in ambient air. Samples were collected using cellulose filters impregnated with oxalic acid, followed by solubilization of the ammonium ion, addition of reagents and fluorimetric detection. Important analytical parameters that were evaluated included sampling time and flow rate. Formaldehyde, diethylamine and hydrogen sulfide did not interfere in the method. The analytical curve was linear up to at least 34 ppbv of ammonia, using a sample flow rate of 0.3 L min(-1) and a sampling time of 20 min. The limit of detection achieved under these conditions was 3 ppbv. The proposed method offers advantages compared to the indophenol colorimetric method, especially the ability to use a shorter sampling time. The method proved to be easy to apply, and should be useful in applications where measurements of low concentrations of ammonia are required, or where there are rapid fluctuations in ammonia concentrations over periods as short as 20 min.
Keywords: gaseous ammonia; acid-impregnated filter; fluorimetric detection; o-phthaldialdehyde; isoindole